A Comprehensive Analysis of Panna Tiger Reserve’s Phenomenal Recovery in Tiger Population after 2009 from Security Viewpoint - Sen, Monali; Jamatia, Naresh (Indian Forester, 2017)
Since the dawn of forestry; management and protection of forest had always been a tricky issue: wherein management of wildlife being the most challenging part of it. This study of scientific management of a Protected Area (PA) (primarily based on security perspective) had taken the example of Panna Tiger Reserve (PTR), Madhya Pradesh. Extensive issues of wild life protection and security issues are analyzed in past, present and future context over a time period of 5 years (viz. 2009 to 2014). The outcome of the study had revealed a case of astonishing achievement and resurrection viz. from the local extinction of Tigers in 2008 to the number of 25 in 2014 and still flourishing with present day number of 32. Strict monitoring, rapid action and fast fallow up of every registered offence taken by the then park authority have brought a revolutionary change in the protection front with a phenomenal incidence of not a single case of Tiger poaching over the timeframe worked upon. Such a stupendous success had established PTR as a pioneering model of holistic management and protection practiced in any PA.